2019
DOI: 10.1177/1474704919879335
|View full text |Cite
|
Sign up to set email alerts
|

Speech Rhythm Convergence as a Social Coalition Signal

Abstract: Patterns of nonverbal and verbal behavior of interlocutors become more similar as communication progresses. Rhythm entrainment promotes prosocial behavior and signals social bonding and cooperation. Yet, it is unknown if the convergence of rhythm in human speech is perceived and is used to make pragmatic inferences regarding the cooperative urge of the interactors. We conducted two experiments to answer this question. For analytical purposes, we separate pulse (recurring acoustic events) and meter (hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…In this sense, the aptitude for joint speech in humans could be linked to the ability for entrainment found in primate communication. Notably, coordination in primate vocal behavior appears to provide a signal of group cohesion and cooperative strength (Ravignani, Bowling, & Fitch, 2014), as also seems to be the case with human beings (Polyanskaya, Samuel, & Ordin, 2019). If we look at the different spheres where joint speech is usededucation, religion, sports, among otherswe find a clear indication that joint speech is used for group cohesion and cooperative strength.…”
Section: Discussionmentioning
confidence: 80%
“…In this sense, the aptitude for joint speech in humans could be linked to the ability for entrainment found in primate communication. Notably, coordination in primate vocal behavior appears to provide a signal of group cohesion and cooperative strength (Ravignani, Bowling, & Fitch, 2014), as also seems to be the case with human beings (Polyanskaya, Samuel, & Ordin, 2019). If we look at the different spheres where joint speech is usededucation, religion, sports, among otherswe find a clear indication that joint speech is used for group cohesion and cooperative strength.…”
Section: Discussionmentioning
confidence: 80%
“…Phonetic convergence, in particular, correlates with a positive evaluation towards the conversational partner, enables communication efficiency, and helps to establish common ground during interactions, reinforcing thus social affiliation (Kousidis et al, 2008(Kousidis et al, , 2009Lee et al, 2010;Louwerse et al, 2012). From a listener's standpoint, the degree of pulse convergence between two interlocutors (but not meter convergence) has been associated with the degree of friendliness and social bonding between them (Polyanskaya et al, 2019; understanding pulse as a regularly recurring acoustic event, and meter as a structured pattern of accentuation of groups of pulses). Furthermore, positive correlations have been found between the amount of involvement in an interaction and the degree of synchrony between interlocutors' f0 and voice intensity level , between the degree of speaking rate convergence and the amount of cooperation during conversations (Manson et al, 2013), and between the amount of convergence of f0 and the degree of learning gain during interactions between students and computer tutors (Thomason et al, 2013).…”
Section: Functionsmentioning
confidence: 99%
“…Further, interlocutors who exhibit high levels of entrainment are rated by their conversation partner as being more competent, persuasive, and likable than those with low levels of entrainment (Chartrand & Barg, 1999;Bailenson & Yee, 2005). Even studies relying on simulated interactions, where confounding factors are eliminated, have shown that entrainment is a beneficial and useful aspect of communication (Polyanskaya et al, 2019;Miles et al, 2009).…”
Section: Introductionmentioning
confidence: 99%